Cataract surgery has minimal effect on corneal shape - Vito Romano; Stephen B Kaye; Keri McLean; Luca Pagano; Esmaeil M Arbabi; Fadi Alfaqawi; Ahmed Al-Maskari; Gabriella Czanner (BMJ Open Ophthalmology)
Purpose To quantify the effect of cataract surgery on cornea shape.Methods Patients undergoing cataract surgery with standardised 2.75 mm surgical incisions at 110 degrees with a side port at 50 degrees were included. Repeat biometric measurements were taken before surgery and at 6 weeks on both operated and unoperated fellow eyes. Data were transformed into Long’s formalism for analysis. Device-specific measurement error was determined. The main outcome measure was the change in keratometry taking into account the change in keratometry of the unoperated fellow eye. Secondary outcome measures included the variability introduced due to location of the incision.Results 132 patients were included. The mean change in keratometry of the operated eye was −0.23@111/+0.21@21 (95% CI −1.43@122/+0.04@32 to +1.04@135/+0.30@45). The flattening effect of the surgical incision was greater and more variable than the steepening effect (p<0.01), particularly if the incision was in the flat meridian. Coupling, defined as ratio of the keratometric change in the preoperative meridians of K2 and K1, varied from 0.91 (SD 2.31) for eyes with an incision in the steep meridian, 0.75 (SD 1.81) for an incision in the flat meridian to 0.28 (SD 2.06) when the incision was made in a neutral meridian.Conclusion Cataract surgery has a slightly greater flattening than steepening effect on corneal shape. Although the effects are very small and variable with incomplete coupling, it is preferable to place the incision in the steep meridian. Greater emphasis, however, should be placed on eye-specific factors, such as biometry, or patient-related factors to optimise refractive outcomes.